Gambling subculture in the Turkish Cypriot community - Macit, Ruken (Journal of Dependence, 2021)
Objective: Many studies reveal the prevalence of gambling addiction among Cypriots. The prevalence of gambling behavior (PPK) in the Turkish Cypriot community stands out as one of the four societies with the highest gambling addiction in the world with the “extremely high” classification. This study aims the historical dimension of the gambling culture in the Turkish Cypriot community and how gambling addiction has been shaped as a subculture in casinos are analyzed. Method: Semi structured interviews were conducted with 20 gamblers and one casino manager living in Cyprus. Qualitative research method was used. Results: The meaning of gambling for gamblers, casino routines (how often they go to the casino, who they go with, what types of gambling they play, their superstitions in gambling) and gamblers’ dreams have been obtained. Conclusion: Contrary to popular belief, the meaning of gambling for gamblers is primarly “pleasure and relaxation. The desire to make Money is seen as the second or third goal. Gambling behavior in the Turkish Cypriot community has gone beyond being an activity aimed at socializing and having fun. It has reached the advanced stages of gambling addiction. The political, social and economic structure of TRNC is the most important factor.